2022
DOI: 10.1155/2022/2420869
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of CH4 Nanoscale Behavior and Enhanced Gas Recovery in Organic-Rich Shale

Abstract: Occurrence and transport are two important nanoscale behaviors in the exploitation of shale gas. Nanopores in a realistic shale organic matrix are composed of kerogen molecules, which will have a great impact on surface-gas interactions and gas nanoconfined behavior. Although there are previous studies, the physics of gas transport through shale systems remains ambiguous. In this work, cylindrical nanopore models representing different pore sizes and organic-rich shale were constructed. By applying the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…After gaining sufficient knowledge about the impact of curvature on methane transportation, we can gradually add more complexities to model the nanochannel. These complexities could include adding functional groups or roughness to the surface of the walls, altering the shape of the cross-section, or even constructing the curved nanochannel by compressing multiple individual kerogen molecules. ,, This progressive approach will allow us to build a more comprehensive and accurate model of the nanochannels in kerogen, enhancing our understanding of methane behavior in these environments.…”
Section: Methodsmentioning
confidence: 99%
“…After gaining sufficient knowledge about the impact of curvature on methane transportation, we can gradually add more complexities to model the nanochannel. These complexities could include adding functional groups or roughness to the surface of the walls, altering the shape of the cross-section, or even constructing the curved nanochannel by compressing multiple individual kerogen molecules. ,, This progressive approach will allow us to build a more comprehensive and accurate model of the nanochannels in kerogen, enhancing our understanding of methane behavior in these environments.…”
Section: Methodsmentioning
confidence: 99%
“…Using a simple model of kerogen in gas shale, in agreement with experimental observations, these authors found that replacing methane by CO 2 is favorable from a thermodynamic viewpoint owing to the strong interactions between CO 2 and kerogen. Since then, by investigating methane/carbon dioxide coadsorption in molecular models of kerogen, many simulation studies have shown that injection of carbon dioxide indeed shifts the adsorption isotherm conditions by favoring the depletion of methane. While the thermodynamic view derived from these works should be complemented by transport coefficients (to fully grasp the complexity of enhanced gas recovery), they already provide a comprehensive view of the problem. Using similar molecular modeling approaches, other authors also considered simple available thermodynamic models to describe methane/carbon dioxide coadsorption in kerogen. , Finally, as an important development beyond thermodynamic modeling, Xu et al have proposed a kinetic model of enhanced gas recovery.…”
Section: Fluid Thermodynamics and Transport In Kerogenmentioning
confidence: 99%
“…With further development of experimental methods, techniques such as elemental analysis, X-ray photoelectron spectroscopy (XPS), and 13 C NMR were used to characterize the elemental composition and functional groups of kerogen to construct a molecular monomer. A dense matrix can be obtained by several kerogen monomers through a series of annealing procedures. Researchers have modified the matrix according to different research purposes: (1) dummy particles were added in the compression process to build a matrix model with a specific porosity , and (2) cutter atoms were introduced to construct different pore shapes in matrix models. Numerous kerogen matrices have been used in gas adsorption isotherm simulations and adsorption-induced kerogen swelling effects. Yu et al used GCMC-MD to compare the volumetric strain caused by the adsorption of CH 4 , C 2 H 6 , and CO 2 . The author suggested that the maximum absolute adsorption capacity of C 2 H 6 was smaller than that of CH 4 and CO 2 , which was attributed to the molecular size.…”
Section: Introductionmentioning
confidence: 99%